Unexpected Detection of Skeletal Muscle Renal Cell Carcinoma Metastasis With 99mTc-EDDA/HYNIC-Tyr3-Octreotide (Tektrotyd) Scan. (27th December 2022) - Fuoco, Valentina; Barisella, Marta; Lorenzoni, Alice; Verzoni, Elena; Maccauro, Marco
Abstract: Somatostatin receptor scintigraphy with 99m Tc-Tektrotyd is widely used for the investigation of neuroendocrine tumors. Overexpression of somatostatin receptors has been shown in different tumor types including lymphomas, breast carcinoma, and renal cell carcinoma (RCC). Isolated case reports have shown that RCC metastases can be identified using somatostatin receptor imaging such as Octreoscan scintigraphy and 68 Ga-DOTATATE PET/CT. We report the case of a 70-year-old man with a history of surgically removed RCC who referred to 99m Tc-Tektrotyd scintigraphy for the evaluation of a pancreatic tail lesion. The scan revealed intense tracer uptake in a left splenius cervicis muscle lesion that on biopsy was consistent with metastatic RCC.